1986
DOI: 10.1128/jvi.60.3.943-949.1986
|View full text |Cite
|
Sign up to set email alerts
|

Failure to detect polyalbumin-binding sites on the woodchuck hepatitis virus surface antigen: implications for the pathogenesis of hepatitis B virus in humans

Abstract: Binding sites for polymerized albumin on hepatitis B virus components were reported in human hepatitis B virus chronic carriers predominantly with active viral replication (HB e antigen positive). The presence of comparable albumin-binding sites in the woodchuck hepatitis virus (WHV) model was examined on WHV components obtained from woodchucks with active viral replication (DNA polymerase positive). Binding sites for polymerized woodchuck serum albumin were not detected on the intact WHV virion, on 22-nm wood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It appears a worthwhile goal to search for cell-culture systems able to bind pHSA or to isolate the pHSA receptors from natural human liver. The hepadnavirus of the woodchuck, however, does not bind natural or polymerized woodchuck serum albumin (39). This shows that albumin binding cannot be a general mechanism of the hepadnaviral life cycle; it prevents use of animal hepadnaviruses for the further study of this phenomenon.…”
Section: Discussionmentioning
confidence: 96%
“…It appears a worthwhile goal to search for cell-culture systems able to bind pHSA or to isolate the pHSA receptors from natural human liver. The hepadnavirus of the woodchuck, however, does not bind natural or polymerized woodchuck serum albumin (39). This shows that albumin binding cannot be a general mechanism of the hepadnaviral life cycle; it prevents use of animal hepadnaviruses for the further study of this phenomenon.…”
Section: Discussionmentioning
confidence: 96%
“…Feitelson et al suggested that besides the major protein bands of SWHs protein, larger proteins with the pre-S sequences were present, but a clear identification was not possible (10). Pohl et al reported that the protein composition of WHsAg from serum was quite similar to those of the pre-S-containing proteins gp33, gp36, p39, and gp42 of HBsAg, but actually the WHs protein band in their silverstained SDS gel corresponding to gp33 of HBsAg was very weak, and the other proteins were not clearly resolved and possibly larger (30). Schaeffer et al identified by immunoblotting with an antiserum against WHV pre-S peptide (residues 85 to 173) four proteins in partially purified WHsAg of 33, 36, 45, and 47 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) The human enhancer I of HBV is obviously not present in the WHV genome (9). (iii) MWHs protein does not bind woodchuck serum albumin (30,34), whereas MHBs protein binds in a species-specific manner modified natural human serum albumin (21). (iv) The LWHs protein is 42 (or 31) amino acids longer than the LHBs protein, due to a larger pre-S1 domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation